PERBANDINGAN HASIL BELAJAR MENGGUNAKAN MODEL PEMBELAJARAN TPS DAN TPT SMAN 1 PALLANGA KABUPATEN GOWA - Abudzar Ghifari; Andi Maulana; Thamrin Tayeb (Jurnal Biotek, 2017)
This thesis discusses cooperative learning model that Think Pair Share and The Power of Two on the subject of the Digestive System Student Class XI SMAN 1 Pallangga. With the aim of research to find out whether there are differences in learning outcomes of students who are taught by koopertaif learning model Think Pair Share and The Power of Two on the subject of the digestive system of class XI student of SMAN 1 Pallangga. This research is experimental form of Quasi Experimental Design (quasi-experimental) design study is a "Posttest-Only Control Design". The study population was all students of class XI SMA Negeri 1 Pallangga. The research sample is class XI IPA4 as an experiment I and class II XI IPA7 as an experiment. Data collection was performed by using the test results in the form posttest study, observation and documentation. Data were analyzed using descriptive analysis techniques and inferential analysis techniques. Analysis of the data shows the results of student learning Class XI SMAN 1 Pallangga on the subject of the digestive system that is taught through cooperative learning model Think Pair Share and The Power of Two. First, the study of students who were taught through cooperative learning model Think Pair Share is in the low category with a percentage of 41.4% of 39 students and an average value of 54.25. Second, the study of students who were taught through cooperative learning model The Power of Two learning at high category with a percentage of 70% of the 30 students with an average value of 66.88. All three of the analytical results of hypothesis testing using t-test, thit value = 4.87 and ttab value = 1.67. Where the value of thit> ttab so H0 rejected, H1 accepted, thus there are differences in the average learning outcomes of students who were taught through cooperative learning model Think Pair Share and types The Power of Two on the subject of the digestive system of class XI SMA Negeri 1 Pallangga Gowa.